2018
DOI: 10.3390/v10120691
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Networks Dysregulation during HTLV-1 Infection and Associated Diseases

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is the causative agent of a neural chronic inflammation, called HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and of a malignant lymphoproliferation, called the adult T-cell leukemia/lymphoma (ATLL). The mechanisms through which the HTLV-1 induces these diseases are still unclear, but they might rely on immune alterations. HAM/TSP is associated with an impaired production of pro-inflammatory cytokines and chemokines, such as IFN-γ, TNF-α, CXCL9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 152 publications
2
58
0
Order By: Relevance
“…This results in the production of TNF-α, IL-6, interferon (IFN)-g and intrathecal antibody, resulting in consequent destruction of glial tissue and neurons, loss of myelin, and fibrillary gliosis. Aye et al (Aye et al, 2000) reported brain perivascular cells infiltration in HAM/TSP and similar chronic lesions are seen in the spine and in the brain (Saito and Bangham, 2012;Futsch et al, 2018). HAM/TSP patients are characterized by elevated levels of IL-4, IL-6, IL-8, IFNg and TNF-α in their plasma and IFN-g, TNF-α, IL-6, and IL-1β in the CSF (Raulino Goncalves et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…This results in the production of TNF-α, IL-6, interferon (IFN)-g and intrathecal antibody, resulting in consequent destruction of glial tissue and neurons, loss of myelin, and fibrillary gliosis. Aye et al (Aye et al, 2000) reported brain perivascular cells infiltration in HAM/TSP and similar chronic lesions are seen in the spine and in the brain (Saito and Bangham, 2012;Futsch et al, 2018). HAM/TSP patients are characterized by elevated levels of IL-4, IL-6, IL-8, IFNg and TNF-α in their plasma and IFN-g, TNF-α, IL-6, and IL-1β in the CSF (Raulino Goncalves et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Since evidence has shown that Tax inhibits UPF1 enzymatic activity by preventing its association with RNA [119], we can hypothesize that other RNA decay pathways that depend on UPF1 are also likely altered, extending the impact of UPF1 on HTLV-1 deregulation. Notably, RMD plays a critical role in immunity and inflammation with the downregulation of multiple transcripts, such as IL-6, IL-2, IL-1b, TNFR2, CD44, and c-Rel, which are also often characterized in HTLV-1 infection [141,156].…”
Section: Discussionmentioning
confidence: 99%
“…As T cells and infected CD4+ T cells in cerebrospinal fluid and neural tissues. It is characterized by a chronic inflammatory state due to elevated cytokine expression and production (reviewed in [13,141]). We wondered whether NMD downregulation, induced for the early infective stage of HTLV-1, may play a role in the later steps of the infection and could converge with ATL or HAM/TSP onset.…”
Section: Htlv-1-associated Pathologies How Can Nmd Inhibition Impactmentioning
confidence: 99%
“…CXCL9 and CXCL10 induce the recruitment of CXCR3 expressing cells including the CXCR3 + IFN-γ producing HTLV-1 infected CD4 + T cells that promote the production of CXCL10 by the astrocytes, creating a positive feedback loop that results in the CNS chronic inflammation (Futsch et al, 2018). In Multiple Sclerosis (MS), which is also a demyelinating neuroinflammatory disease, it is thought that CXCL9 and CXCL10 in the CSF are involved in the recruitment of CXCR3 + T cells into CNS and contribute to MS pathogenesis (Müller et al, 2010;Cheng and Chen, 2014;Vazirinejad et al, 2014;Koper et al, 2018).…”
Section: Cxcl9 and Cxcl10mentioning
confidence: 99%